DETERMINANT OF LENGTH OF NEW BORN - Budiarti, Tri (STIKes Kapuas Raya, 2019)
The condition of pregnant women greatly determines the condition of fetal growth and development both during the womb and at birth. Baby growth when in the womb is linearly indicating the length of the baby at birth, which if the length of birth is short (stunting) indicates a state of malnutrition. The impact of stunting in addition to a short physical will affect cognitive function so that the quality of life decreases. Cilacap Hospital is one of the referral hospitals at the Cilacap Regency level with 2,384 babies born in 2017. Cilacap is a district in Central Java that is prone to stunting. This study aims to determine the determinants or factors that affect the birth length of the baby including birth weight, gestation, and anemia status of the mother during pregnancy. The research method used was observational with a cross sectional design with a sample of 331 taken from medical records in Cilacap Hospital. The research method used was observational with a cross sectional design with a sample of 331 taken from medical records in Cilacap Hospital and analyzed by the chi square formula. The results of p values between birth weight, gestation, and maternal anemia status during pregnancy on birth length <significant level at alpha 0.05. The conclusion is that there is no relationship between birth weight, gestation, and anemia status of the mother during pregnancy with birth length so that all three are not factors that affect the length of birth of the baby.